Epileptic seizures heralding a relapse in high grade gliomas. (October 2017) - Di Bonaventura, Carlo; Albini, Mariarita; D'Elia, Alessandro; Fattouch, Jinane; Fanella, Martina; Morano, Alessandra; Lucignani, Giulia; Manfredi, Mario; Colonnese, Claudio; Salvati, Maurizio; Vanacore, Nicola; Berardelli, Alfredo; et al.
Highlights: Seizures are a common clinical symptom in high-grade gliomas (HGG). Seizures may herald high grade glioma relapse (HGG-R) preceding its MRI evidence. Interval between seizure and HGG-R is associated with CT cycles and follow-up duration. By combining these factors, it may be possible to estimate the timing of HGG-R. Seizures should always be considered as a red flag during follow-up in patients with HGG. Abstract: Purpose: Seizures are a common clinical symptom in high-grade gliomas (HGG). The aim of the study was to investigate the relationship between seizures and HGG relapse (HGG-R). Methods: We retrospectively evaluated 145 patients who were surgically treated for HGG-R. By analyzing clinical characteristics in these patients (all operated and treated by the same protocol), we identified 37 patients with seizures during follow-up. This cohort was divided into four subgroups according to a) presence or absence of seizures at the time of diagnosis and b) temporal relationship between seizure occurrence and HGG-R during follow-up: subgroup A (25 pts) had seizures at follow-up but not at onset, subgroup B (12 pts) had seizures both at follow-up and onset, subgroup C (30 pts) had seizures before MRI-documented HGG-R, and subgroup D (7 pts) had seizures after MRI-documented HGG-R. Results: Although the datum was not statistically significant, survival was longer in patients with seizures during follow-up than in those without seizures (59.3% vs 51.4% alive at 2 years). In 30 patients (subgroup C) seizures heralded HGG-R. In a correlation analysis for this last subgroup, the time interval between seizure and the HGG-R was significantly associated with the number of chemotherapy cycles (r = 0.470; p = 0.009) and follow-up duration (r = 0.566; p = 0.001). A linear regression model demonstrated a reciprocal association between the above factors and that it may be possible to estimate the timing of HGG-R by combining these data. Conclusions: Seizures may herald HGG-R before MRI detection of relapse, thus suggesting that seizures should always be considered a red flag during follow-up.